G157(P) Impact of paediatrician with cardiology expertise on ambulatory ECG requests. (27th April 2016) - Mikrou, P; Ramcharan, T; Ramesh, P
Abstract : Aims: We aimed to assess the impact of a Paediatrician with Cardiology Expertise (PEC) on ambulatory ECG requests at a large University Teaching Hospital. Methods: We conducted a retrospective study comparing ambulatory ECG requests before and after the appointment of a PEC (November 2013–October 2014 versus November 2014–October 2015). We analysed the data for a) number of requests, b) clinical indication, c) referral source, and d) result of ambulatory ECG monitoring. Patients with underlying congenital heart defects or known arrhythmias were excluded. Results: The appointment of a PEC resulted in 23% reduction in ambulatory ECG requests (31 vs. 24) in a 12-month period. Since the appointment, the PEC made 42% of the total referrals. Indications for ambulatory ECG included palpitations, syncope/pre-syncope, chest pain and abnormal 12-lead ECGs (Table 1 ). Abnormal results requiring tertiary Paediatric Cardiology follow-up were identified in 20% of tapes, both in the pre- and post-PEC clinic period. However 3 out of 4 abnormal tapes (75%) were referred by the PEC with the 4th case being an inpatient with a documented SVT on the 12-lead ECG in the Paediatric ward. Conclusion: This study has shown that the appointment of a PEC had a positive impact on reducing the number of ambulatory ECG requests within the first 12 months of their employment, making the service more cost-effective. Although the diagnostic yield of ambulatory ECGs has not changed significantly, the majority of tapes with abnormal electrocardiographical results were referred by the PEC. With the role of PECs becoming an established part of paediatric services, the burden of unnecessary and costly investigations to cardiology is expected to be relieved. This will subsequently lead to positive economic and clinical outcomes.